2011
DOI: 10.1111/j.1099-1123.2011.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditor's Gender and Audit Fees

Abstract: Documented behavioral differences between women and men suggest that the gender of the audit engagement partner may have implications for the price setting of the audit. Thus, this paper examines the effect of the auditor's gender on audit fees in an environment where the responsible audit partners can be identified. Using a sample of public firms from the NASDAQ OMX exchanges in three Nordic countries, we find evidence indicating that firms with female audit engagement partners have significantly higher audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 46 publications
5
58
1
9
Order By: Relevance
“…The findings are somewhat consistent with our prediction that the presence of women directors on firms' board of directors is less likely to utilise accretive share buyback to manage EPS. The result is also slightly consistent with the argument that women are more conservative and less risk tolerance than a man in making decisions related to managing earnings (Ittonen & Peni, 2012;Krishnan & Parsons, 2008;Peni & Vähämaa, 2010). Practically, the results of this ISSN 1946-052X 2017 paper support the policy of the Malaysian government to increase the presence of women in decision-making positions to become 30 percent in both public and private sectors.…”
Section: Multivariate Analysissupporting
confidence: 77%
“…The findings are somewhat consistent with our prediction that the presence of women directors on firms' board of directors is less likely to utilise accretive share buyback to manage EPS. The result is also slightly consistent with the argument that women are more conservative and less risk tolerance than a man in making decisions related to managing earnings (Ittonen & Peni, 2012;Krishnan & Parsons, 2008;Peni & Vähämaa, 2010). Practically, the results of this ISSN 1946-052X 2017 paper support the policy of the Malaysian government to increase the presence of women in decision-making positions to become 30 percent in both public and private sectors.…”
Section: Multivariate Analysissupporting
confidence: 77%
“…Ittonen and Peni (2012) found that female auditors in Denmark, Sweden and Finland charged a higher price for audit services than male auditors. We also expect that auditors with longer experience of the audit profession could charge a higher price than less experienced auditors.…”
Section: Audit and Non-audit Feesmentioning
confidence: 96%
“…The effect of AIC characteristics on audit quality has recently received substantial attention in the audit literature (Goodwin, 2012;Ittonen and Peni, 2012;Gul et al, 2013;Ittonen et al, 2013;Sundgren and Svanström, 2014). Ittonen and Peni (2012) found that female auditors in Denmark, Sweden and Finland charged a higher price for audit services than male auditors.…”
Section: Audit and Non-audit Feesmentioning
confidence: 99%
“…Two relevant studies investigating companies in Belgium and in three Nordic countries found that women audit partners earn higher audit fees, perhaps due to higher independence (Hardies, Breesch, & Branson, 2010), better diligence, and less overconfidence (Ittonen and Peni, 2012). These findings suggest that sex stereotypes may vary across cultures and that discrimination against women in the workplace is less severe in Northern European countries as compared to Taiwan, where Confucianism advocates the masculine social value that women should stay at home and be responsible for the household, while men are the breadwinners and leaders of the family (Chan et al, 2002;Yang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%